2018
DOI: 10.1371/journal.pone.0200291
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland carcinoma: Prediction of cancer death risk based on apparent diffusion coefficient histogram profiles

Abstract: We evaluated apparent diffusion coefficient (ADC) histogram parameters for predicting the outcomes of patients with salivary gland carcinoma. Diffusion-weighted MR imaging was performed in 20 patients with salivary gland carcinoma, and ADCs were determined using b-values of 500 and 1000 s/mm2. ADC histogram parameters (mean, median, percentage tumor area with distinctive ADC values [pADC], skewness, and kurtosis) were analyzed. The patients were followed for 5–136 months after primary surgery. The ADC histogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Although useful MRI findings to differentiate between benign and malignant salivary gland tumors and indicate the histological subtypes of salivary gland cancer have been reported, [10][11][12][13][14] few reports have described the relationship between MRI findings and patient prognosis. Sumi and Nakamura 15 reported that apparent diffusion coefficient (ADC) histogram analysis, especially percentage tumor area with distinctive ADC values, was helpful in predicting cancer-related deaths in patients with salivary gland cancer; however, histogram analysis is not suitable for routine daily practice. Hence, this study aimed to evaluate the utility of pretreatment MRI parameters using conventional imaging sequences and determine the prognostic factors in predicting the clinical outcomes of patients with parotid gland cancer.…”
mentioning
confidence: 99%
“…Although useful MRI findings to differentiate between benign and malignant salivary gland tumors and indicate the histological subtypes of salivary gland cancer have been reported, [10][11][12][13][14] few reports have described the relationship between MRI findings and patient prognosis. Sumi and Nakamura 15 reported that apparent diffusion coefficient (ADC) histogram analysis, especially percentage tumor area with distinctive ADC values, was helpful in predicting cancer-related deaths in patients with salivary gland cancer; however, histogram analysis is not suitable for routine daily practice. Hence, this study aimed to evaluate the utility of pretreatment MRI parameters using conventional imaging sequences and determine the prognostic factors in predicting the clinical outcomes of patients with parotid gland cancer.…”
mentioning
confidence: 99%